TO THE PROBLEM OF CULTURE FORMATION COMMUNICATION OF FUTURE TEACHERS - Lysevich, O.V. (Pedagogy of Higher and Secondary Education, 2022)
This article reveals the problem of formation of communicative culture in dialogue studying situations.